The activity of satellite cells and myonuclei following 8 weeks of strength training in young men with suppressed testosterone levels. (15th November 2014) - Kvorning, T.; Kadi, F.; Schjerling, P.; Andersen, M.; Brixen, K.; Suetta, C.; Madsen, K.
Abstract Aim To investigate how suppression of endogenous testosterone during an 8‐week strength training period influences the activity of satellite cells and myonuclei. Methods Twenty‐two moderately trained young men participated in this randomized, placebo‐controlled, and double‐blinded intervention study. The participants were randomized to treatment with a GnRH analogue, goserelin (n = 12), which suppresses testosterone or placebo (n = 10) for 12 weeks. The strength training period of 8 weeks started after 4 weeks of treatment and included exercises for all major muscles. Biopsies were obtained from the mid‐portion of the vastus lateralis muscle. Results Testosterone resting level in goserelin was 10–20 times lower compared with placebo, and the training‐induced increase in the level of testosterone was abolished in goserelin. Training increased satellite cells number in type II fibres by 20% in placebo and by 52% in goserelin (P < 0.01), whereas the myonuclear number significantly increased by 12% in type II fibres in placebo and remained unchanged in goserelin (P < 0.05). No changes in satellite cells and myonuclei were seen in type I fibres in either group. Data from the microarray analysis indicated that low testosterone affects the bone morphogenetic proteins signalling, which might regulate proliferation vs. differentiation of satellite cells. Conclusion Eight weeks of strength training enhances the myonuclear number in type II fibres, and this is largely blocked by the suppression of testosterone. The data indicate that low testosterone levels could reduce the differentiation of satellite cells to myonuclei via the bone morphogenetic proteins signalling pathway, resulting in reduced increases in lean leg mass.